2004
DOI: 10.1029/2003ja010138
|View full text |Cite
|
Sign up to set email alerts
|

Cluster observations of quasi‐periodic impulsive signatures in the dayside northern lobe: High‐latitude flux transfer events?

Abstract: [1] We report on a series of quasi-periodic reversals in GSM B Z observed by the four Cluster spacecraft in the northern dayside lobe poleward of the cusp on 23 February 2001. During an interval of about 35 min, multiple reversals (negative to positive) in B Z of approximately 1-min duration with an approximate 8-min recurrence time were observed. The individual structures do not resemble low-latitude flux transfer events (FTE) but the 8-min recurrence frequency suggests that intermittent reconnection may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…Our study was based on just one event, reserving an analysis of many events for future work. We note, however, that in a very recent work Thompson et al (2004) observed the same type of impulsive events, though they discussed them only from the Cluster perspective. The focus there was on a sequence of reversals of the GSM B z field component observed downstream of the cusp, each reversal being ascribed to currents flowing perpendicular to the field.…”
Section: The Observations In the Context Of Solar Windmagnetosphere Imentioning
confidence: 91%
“…Our study was based on just one event, reserving an analysis of many events for future work. We note, however, that in a very recent work Thompson et al (2004) observed the same type of impulsive events, though they discussed them only from the Cluster perspective. The focus there was on a sequence of reversals of the GSM B z field component observed downstream of the cusp, each reversal being ascribed to currents flowing perpendicular to the field.…”
Section: The Observations In the Context Of Solar Windmagnetosphere Imentioning
confidence: 91%
“…The event exhibited near monopolar signatures in the X and Z components of the magnetic field. Finally, Thompson et al (2004) interpreted Cluster observations of a series of transient events that occurred poleward of the northern cusp just prior to local noon as evidence for FTEs. A reversal in B z , but no magnetic field strength increase or bipolar signature normal to the nominal magnetopause, marked each event.…”
Section: Discussionmentioning
confidence: 99%
“…A reversal in B z , but no magnetic field strength increase or bipolar signature normal to the nominal magnetopause, marked each event. As they are not classic examples of FTEs, we did not include events of the type reported by Berchem et al (1995), Sonnerup et al (2004), or Thompson et al (2004) in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2005) suggested that this was because FTEs were more likely to extend further out into the magnetosheath than they extend into the magnetosphere; recent analysis of some individual FTEs observed by Cluster has confirmed that this may be the case (Hasegawa et al, 2006). However, a further possible explanation is that the magnetospheric signatures of FTEs at high latitudes, particularly in the vicinity of the cusp, may often be more complicated than low latitude signatures, possibly leading to an underestimate of the number of magnetospheric events (Thompson et al, 2004;Fear et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%